Sodium-ion battery positive electrode material, preparation method and application

By reacting iron with raw materials such as phosphoric acid and citric acid and mixing it with sodium source, Na4Fe3(PO4)2P2O7/C composite material is prepared using a new synthesis route, which solves the problems of high raw materials and high impurity content in the prior art, and achieves the preparation of positive electrode materials with excellent performance and low cost.

CN119591068APending Publication Date: 2025-03-11CHEM & CHEM ENG GUANGDONG LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411258324.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing Na4Fe3(PO4)2P2O7 positive electrode material synthesis methods have problems such as high raw material prices and high impurity content, resulting in high production costs.

Method used

A new synthesis route is adopted to react iron with phosphoric acid solution to form a mixed solution, then react iron with citric acid solution to form a suspension, and hydrogen peroxide is added or air is introduced, and finally mixed with the sodium source is evenly formed, and carbon-containing composite material is obtained after drying and sintering.

Benefits of technology

It is realized to prepare pure phase carbon-containing composite materials with excellent performance from low-cost raw materials, with simple synthesis routes and fewer impurities, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591068A_ABST
    Figure CN119591068A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode material, a preparation method and application, and the preparation method comprises the following steps: S1, reacting iron with a phosphoric acid solution to form a mixed solution of phosphoric acid and ferrous dihydrogen phosphate as a solution A; s2, reacting iron with a citric acid solution to form a turbid liquid, and then adding hydrogen peroxide for mixing or introducing air to obtain a solution B; s3, uniformly mixing the solution A, the solution B and a sodium source to obtain a solution C; s4, drying the solution C to obtain precursor powder, and sintering to obtain a carbon-containing composite material; wherein in the steps S1-S3, in the sodium source, the iron and the phosphoric acid, the molar ratio of the sodium element to the iron element to the phosphorus element is 4: 3: 4. The pure-phase carbon-containing composite material with excellent performance is prepared from low-cost raw materials, the synthesis route is simple, impurities are few, and the production cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material, a preparation method and an application thereof. Background Art

[0002] The shortage of fossil energy and the environmental pollution caused by burning fossil fuels have promoted the development of green and clean electrochemical energy storage technology. Currently, lithium-ion batteries have been widely used in convenient electronic devices, electric vehicles and other fields due to their advantages such as high safety, high energy density and long cycle life. Exploring other battery systems with richer resources and lower costs is gaining increasing attention.

[0003] Sodium resources have the advantages of wide abundance and low price, and sodium and lithium have similar electrochemical properties, so sodium-ion batteries are expected to become an ideal substitute for lithium-ion batteries. The main cathode materials for sodium-ion batteries are transition metal oxides, polyanionic compounds, organic compounds and Prussian blue analogs. Among them, the iron-based mixed polyanionic compound Na4Fe3(PO4)2P2O7 has a high theoretical specific capacity (129mAh g -1 ), high structural stability, high safety and low cost, etc., and has been widely studied, becoming the most commercially promising positive electrode material for sodium-ion batteries. However, the existing synthesis methods of Na4Fe3(PO4)2P2O7 have the problems of high raw material prices and high impurity content. Therefore, it is necessary to propose a new synthesis route. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a sodium ion battery positive electrode material, a preparation method and an application, so as to prepare a pure phase carbon-containing composite material with excellent performance using low-cost raw materials, with a simple synthesis route and few impurities, which is conducive to reducing production costs.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0006] In the first aspect of the present invention, the present invention proposes a method for preparing a positive electrode material for a sodium ion battery, which is as follows:

[0007] S1, reacting iron with a phosphoric acid solution to form a mixed solution of phosphoric acid and ferrous dihydrogen phosphate as solution A;

[0008] S2, reacting iron with citric acid solution to form a suspension, then adding hydrogen peroxide to mix or introducing air to obtain solution B;

[0009] S3, mixing solution A, solution B and a sodium source uniformly to obtain solution C;

[0010] S4, drying solution C to obtain a precursor powder, and sintering to obtain a carbon-containing composite material;

[0011] Wherein, in steps S1-S3, the molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron and phosphoric acid is 4:3:4.

[0012] Preferably, in step S1, the molar ratio of phosphoric acid to iron is (2.5-5):1, more preferably, the molar ratio of phosphoric acid to iron is (2.5-3.5):1.

[0013] Preferably, in step S2, the molar ratio of citric acid to iron is (1-5):1, the molar ratio of hydrogen peroxide to iron in hydrogen peroxide is (1.5-8):1, and more preferably, the molar ratio of hydrogen peroxide to iron in hydrogen peroxide is (1.5-5):1.

[0014] Preferably, in step S3, the sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate, disodium monohydrogen phosphate, sodium hydroxide, sodium citrate, sodium nitrate and sodium pyrophosphate.

[0015] Preferably, in step S4, the sintering temperature is 400-600°C, more preferably, the sintering temperature is 500-600°C; the heating rate during sintering is ≤10°C / min, more preferably, the heating rate during sintering is ≤5°C / min; the sintering time is 6-16h, further, the sintering time is 8-12h.

[0016] Preferably, in step S3, solution A, solution B, a sodium source and a soluble manganese source are mixed uniformly to obtain solution C, wherein the molar ratio of the sum of iron element and manganese element to sodium element and phosphorus element is 3:4:4.

[0017] More preferably, step S4 further includes a pre-burning operation, including:

[0018] After the solution C is dried, the precursor powder obtained by drying is pre-fired in a protective gas, and the pre-fired powder is then sintered, wherein the pre-fired temperature is 380-390° C., the pre-fired time is 2-5 h, and the heating rate is 2-5° C. / min.

[0019] In the second aspect of the present invention, the present invention provides a sodium ion battery positive electrode material, and the Na4Fe3(PO4)2P2O7 / C composite material is prepared by the above method.

[0020] In the third aspect of the present invention, the present invention provides a sodium ion battery positive electrode material, prepared by the above method Na4Fe x Mn 3-x (PO4)2P2O7 / C composite material, 0<x<3.

[0021] In a fourth aspect of the present invention, the present invention provides an application of a positive electrode material for a sodium ion battery, wherein the composite material prepared above is used to prepare a sodium ion battery.

[0022] Beneficial effects:

[0023] The present invention uses relatively low-cost raw materials to prepare a pure-phase carbon-containing composite material with excellent performance, has a simple synthesis route and few impurities, and provides a new idea for the research and development of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The XRD diagrams of the composite materials prepared in Examples 1-7 of the present invention are shown.

[0025] Figure 2 This is a SEM image of the composite material prepared in Example 1 of the present invention.

[0026] Figure 3 This is a SEM image of the composite material prepared in Example 7 of the present invention. DETAILED DESCRIPTION

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.

[0028] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, which is specifically as follows:

[0029] S1, reacting iron with an excess phosphoric acid solution to form a mixed solution of phosphoric acid and ferrous dihydrogen phosphate as solution A;

[0030] S2, reacting the iron with the citric acid solution to form a suspension, and then adding 30% by mass of hydrogen peroxide to mix or introducing air to obtain a solution B;

[0031] S3, mixing solution A, solution B and a sodium source uniformly to obtain solution C;

[0032] S4. Drying the solution C to obtain a precursor powder, and sintering the precursor powder in a protective gas to obtain a carbon-containing composite material.

[0033] The product obtained by the above scheme is a Na4Fe3(PO4)2P2O7 / C composite material.

[0034] In step S1, phosphoric acid reacts, which is the main source of phosphorus in the product. The iron reacts with excess phosphoric acid to completely dissolve the iron and generate soluble ferrous dihydrogen phosphate. Preferably, the molar ratio of phosphoric acid to iron is (2.5-5):1, and more preferably, the molar ratio of phosphoric acid to iron is (2.5-3.5):1. It is necessary to ensure that phosphoric acid is excessive. When phosphoric acid is not excessive, solution A will have obvious precipitation and cannot be used.

[0035] In step S1, the concentration of phosphoric acid is 10-80 wt.%, and the temperature of the reaction between phosphoric acid and iron is 50-100°C.

[0036] In step S2, iron reacts with citric acid to generate slightly soluble ferrous citrate, and ferrous ions are oxidized to ferric ions by adding hydrogen peroxide or passing air to generate soluble ferric citrate; hydrogen peroxide also reacts with citrate under acidic conditions to consume the carbon content in the solution. It is easy to understand that, in theory, 2 mol of citric acid reacts with 3 mol of iron, that is, when citric acid and iron react in a molar ratio of 1:1, citric acid is excessive for iron, so in step S2, citric acid is excessive compared to iron, and excess citric acid can be used as a carbon source to increase the carbon content in the final product, hydrogen peroxide is sufficient or excessive compared to iron, hydrogen peroxide preferentially oxidizes ferrous ions, and excess hydrogen peroxide reacts with citric acid to consume part of the citric acid.

[0037] The source of C in the product Na4Fe3(PO4)2P2O7 / C composite material is determined by controlling the amount of hydrogen peroxide used to control the extent of consumption of the citrate by the reaction, thereby controlling the C in the composite material.

[0038] Preferably, in step S2, the molar ratio of citric acid to iron is (1-5):1, the molar ratio of hydrogen peroxide to iron in hydrogen peroxide is (1.5-8):1, and preferably, the molar ratio of hydrogen peroxide to iron in hydrogen peroxide is (1.5-5):1. In step S2, the temperature of the reaction of citric acid and iron is 50-100°C.

[0039] Step S3 is to make the sodium element enter the system, and the sodium source is a soluble sodium salt, such as sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate, disodium monohydrogen phosphate, sodium hydroxide, sodium citrate, sodium nitrate and sodium pyrophosphate. One or more. It is easy to understand that when the sodium source is sodium carbonate, sodium bicarbonate and sodium hydroxide, the acid in the mixed solution reacts with the sodium source, the sodium ions are dissolved in the solution, and water (and carbon dioxide) are generated, and no impurity ions enter the system; when the sodium source is sodium acetate, sodium citrate and sodium nitrate, anions are present in the solution and converted into gas during calcination later, wherein the organic acid radical in organic sodium (such as sodium acetate and sodium citrate) can introduce carbon to increase the carbon content of the final product; when the sodium source is sodium dihydrogen phosphate, disodium monohydrogen phosphate and sodium pyrophosphate, the anion part is also required by the system, which has little effect on the preparation.

[0040] In step S3, the mixing method can be various, such as mixing solution A and solution B first, and then adding the sodium source, or dissolving the sodium source in solution A first, and then adding solution B to mix evenly, or dissolving the sodium source in solution B first, and then adding solution A to mix evenly, or mixing solution A, solution B and the sodium source at the same time.

[0041] It should be noted that when the sodium source reacts with the acid in the system (i.e., the sodium source is sodium carbonate, sodium bicarbonate, and sodium hydroxide), the sodium source cannot be mixed with solution A or B first, because the addition of the sodium source will affect the pH value of the system, resulting in precipitation of ferrous ions or ferric ions. Preferably, the sodium source is added by slowly dropping the sodium source solution after solution A is mixed with solution B. When the sodium source does not change the pH value of solution A or B, the sodium source can be mixed with solution A or B first, or can be added after solution A and solution B are mixed. Preferably, the sodium source is added after solution A and solution B are mixed.

[0042] It should be noted that the raw materials (iron and phosphoric acid) in step S1 and the raw materials (iron, citric acid and hydrogen peroxide) in step S2 cannot be directly mixed, because the reaction product of iron and citric acid is slightly soluble in water and is converted into soluble ferric citrate under the oxidation of hydrogen peroxide, but direct mixing will cause the ferrous ions in the solution to be oxidized and combined with phosphate to form iron phosphate precipitation. Therefore, the present invention prepares solution A and solution B separately.

[0043] In addition, in the process of preparing solution B, the amount of hydrogen peroxide added is controlled. After the hydrogen peroxide reacts with the ferrous ions, the remaining hydrogen peroxide can react with the excess citric acid to achieve complete consumption, thereby avoiding affecting the ferrous ions in solution A.

[0044] In steps S1-S3, the molar ratio of sodium, iron and phosphoric acid is 4:3:4, so as to meet the stoichiometric ratio of sodium, iron and phosphorus in the composite material. It is easy to understand that when the sodium source is sodium dihydrogen phosphate, disodium monohydrogen phosphate and sodium pyrophosphate, the sodium source contains both sodium and phosphorus, so the amount of phosphoric acid in step S1 is reduced, and at the same time, the amount of iron in step S1 is appropriately reduced to meet the requirement of excessive phosphoric acid, and the amount of iron reduced in step S1 can be increased accordingly in step S2, that is, the amount of corresponding raw materials in each step is adjusted according to the requirement that the molar ratio of sodium, iron and phosphorus is 4:3:4.

[0045] Preferably, in step S4, the outlet air temperature in the spray drying stage is 100-150°C.

[0046] Preferably, in step S4, the sintering temperature is 400-600°C, more preferably, the sintering temperature is 500-600°C; the heating rate during sintering is ≤10°C / min, more preferably, the heating rate during sintering is ≤5°C / min; the sintering time is 6-16h, further, the sintering time is 8-12h.

[0047] Step S4 also includes a pre-firing operation. Specifically, after spray drying the solution C, the precursor powder obtained by spray drying is pre-firing in a protective gas, and the pre-firing powder is ground and then sintered in a protective gas. The pre-firing temperature is 380-390°C, the pre-firing time is 2-5h, and the heating rate is 2-5°C / min.

[0048] The protective gas of the present invention is preferably an inert gas such as argon or nitrogen. The iron source used in the present invention is iron powder, preferably with a particle size of 100 to 300 meshes.

[0049] After sintering, the citrate and other carbon-containing components in solution C are converted into carbon-coated Na4Fe3(PO4)2P2O7, thereby improving the conductivity of the composite material.

[0050] As a more preferred solution, in step S3, solution A, solution B, a sodium source and a manganese source are mixed uniformly to obtain solution C. Preferably, in order not to affect the stability of iron ions and ferrous ions in the system, solution A and solution B are preferentially mixed, and then a soluble manganese source is added, and after the manganese source is dissolved, a sodium source is added, and stirred uniformly to obtain solution C, wherein the molar ratio of the sum of the iron element and the manganese element to the sodium element and the phosphorus element is 3:4:4. Preferably, the manganese source includes one or more of manganese dihydrogen phosphate, manganese acetate, manganese sulfate, manganese nitrate, and manganese oxalate.

[0051] After adding the manganese source, the final carbonaceous composite material is Na4Fe x Mn 3-x(PO4)2P2O7 / C, 0<x<3, better conductivity. For example, manganese-containing carbon composite materials can be Na4Fe 2.5 Mn 0.5 (PO4)2P2O7 / C, Na4Fe2Mn(PO4)2P2O7 / C, Na4Fe 1.5 Mn 1.5 (PO4)2P2O7 / C, Na4FeMn2(PO4)2P2O7 / C.

[0052] The technical solution of the present invention is described in detail below with specific embodiments.

[0053] Example 1

[0054] S1. Take a phosphoric acid solution containing 0.1 mol of phosphoric acid and a mass fraction of 85%, add an appropriate amount of water to prepare a phosphoric acid solution with a concentration of 30 wt.%, add 1.8617 g (about 0.0333 mol) of 300-mesh iron powder to the phosphoric acid with a molar ratio of iron element to phosphorus element of 1:3, keep warm at 80°C with continuous stirring, and react for 0.5 h to obtain solution A;

[0055] S2, take 0.0417mol of citric acid and dissolve it in an appropriate amount of water to prepare a citric acid solution with a concentration of 10wt.%, add 2.3271g (about 0.0417mol) of 300-mesh iron powder to the citric acid solution according to the molar ratio of iron powder to citric acid of 1:1, keep warm at 80°C with continuous stirring, react for 4h to obtain a suspension, then add 7.5ml (about 0.0734mol of hydrogen peroxide) with a mass fraction of 30%, react for 0.5h to obtain solution B;

[0056] S3, solution A and solution B are mixed evenly, and then a sodium carbonate solution containing 0.05 mol of sodium carbonate is slowly added dropwise to the solution, wherein the molar ratio of sodium to iron in the solution is 4:3, and after sufficient stirring, a uniform dark green solution C is obtained;

[0057] S4. Solution C is spray-dried to obtain a precursor powder with an outlet temperature of 120°C. The precursor powder is then placed in argon protection and pre-fired at 380°C for 3 hours with a heating rate of 5°C / min. The pre-fired powder is ground and then sintered in argon with a heating rate of 5°C / min. It is kept at 565°C for 10 hours to obtain a finished Na4Fe3(PO4)2P2O7 / C composite material.

[0058] Example 2

[0059] Compared with Example 1, the final firing temperature in step S4 is adjusted to 550° C. in this example, and the remaining operations are the same as those in Example 1.

[0060] Example 3

[0061] Compared with Example 1, the final firing temperature in step S4 is adjusted to 500° C. in this example, and other operations are the same as those in Example 1.

[0062] Example 4

[0063] Compared with Example 1, the amount of hydrogen peroxide added in step S2 is changed to 15 ml (about 0.1468 mol hydrogen peroxide), and the remaining operations are the same as those in Example 1.

[0064] Example 5

[0065] Compared with Example 1, the amount of hydrogen peroxide added in step S2 is changed to 22.5 ml (about 0.2202 mol hydrogen peroxide), and the remaining operations are the same as those in Example 1.

[0066] Example 6

[0067] S1. Take a phosphoric acid solution containing 0.1 mol of phosphoric acid and a mass fraction of 85%, add an appropriate amount of water to prepare a phosphoric acid solution with a concentration of 30 wt.%, add 1.8617 g (about 0.0333 mol) of 300-mesh iron powder to the phosphoric acid with a molar ratio of iron element to phosphorus element of 1:3, keep warm at 60°C with continuous stirring, and react for 1 hour to obtain solution A;

[0068] S2, take 0.0417mol of citric acid and dissolve it in an appropriate amount of water to prepare a citric acid solution with a concentration of 10wt.%, add 2.3271g of 300-mesh iron powder to the citric acid solution according to the molar ratio of iron powder to citric acid of 1:1, keep warm at 60°C with continuous stirring, react for 6h to obtain a suspension, then add 7.5ml of 30% hydrogen peroxide, react for 0.5h to obtain solution B;

[0069] S3, solution A and solution B are mixed evenly, and then a sodium carbonate solution containing 0.05 mol of sodium carbonate is slowly added dropwise to the solution, wherein the molar ratio of sodium to iron in the solution is 4:3, and after sufficient stirring, a uniform dark green solution C is obtained;

[0070] S4. Solution C is spray-dried to obtain a precursor powder with an outlet temperature of 120°C. The precursor powder is then placed in argon protection and pre-fired at 380°C for 3 hours with a heating rate of 5°C / min. The pre-fired powder is ground and then sintered in argon with a heating rate of 5°C / min. It is kept at 565°C for 10 hours to obtain a finished Na4Fe3(PO4)2P2O7 / C composite material.

[0071] Example 7

[0072] Compared with Example 1, the sintering process in step S4 of this embodiment is adjusted to a one-step sintering process, that is, the precursor powder obtained by spray drying is placed in an argon protection, and the temperature is raised to 565°C at a rate of 5°C / min and kept at this temperature for 10 hours to obtain the finished product Na4Fe3(PO4)2P2O7 / C composite material

[0073] Example 8

[0074] S1. Take a phosphoric acid solution containing 0.05 mol of phosphoric acid and a mass fraction of 85%, add an appropriate amount of water to prepare a phosphoric acid solution with a concentration of 30 wt.%, add 0.9309 g (about 0.0167 mol) of 300-mesh iron powder to the phosphoric acid with a molar ratio of iron element to phosphorus element of 1:3, keep warm at 80°C with continuous stirring, react for 0.5 h, and obtain solution A;

[0075] S2, take 0.0333 mol of citric acid and dissolve it in an appropriate amount of water to prepare a citric acid solution with a concentration of 10wt.%, add 0.0333 mol of 300 mesh iron powder to the citric acid solution according to the molar ratio of iron powder to citric acid of 1:1, keep warm at 60°C with continuous stirring, react for 4 hours to obtain a suspension, then add 6 ml of 30% hydrogen peroxide, react for 0.5 hours to obtain solution B;

[0076] S3, solution A and solution B were mixed evenly, 0.025 mol of manganese dihydrogen phosphate was added, and after it was completely dissolved, a sodium carbonate solution containing 0.05 mol of sodium carbonate was slowly added dropwise to the solution, wherein the molar ratio of the sum of iron and manganese in the solution to sodium was 3:4, and after sufficient stirring, a uniform dark green solution C was obtained;

[0077] S4. Solution C is spray-dried to obtain a precursor powder with an outlet temperature of 120°C. The precursor powder is then placed in argon protection and pre-fired at 380°C for 3 hours with a heating rate of 5°C / min. The pre-fired powder is ground and then sintered in argon with a heating rate of 5°C / min. It is kept at 565°C for 10 hours to obtain a finished product Na4Fe2Mn(PO4)2P2O7 / C composite material.

[0078] Example 9

[0079] S1. Take a phosphoric acid solution containing 0.05 mol of phosphoric acid and a mass fraction of 85%, add an appropriate amount of water to prepare a phosphoric acid solution with a concentration of 30 wt.%, add 0.9309 g (about 0.0167 mol) of 300-mesh iron powder to the phosphoric acid with a molar ratio of iron element to phosphorus element of 1:3, keep warm at 80°C with continuous stirring, react for 0.5 h, and obtain solution A;

[0080] S2, take 0.0583 mol of citric acid and dissolve it in an appropriate amount of water to prepare a citric acid solution with a concentration of 10wt.%, add 0.0583 mol of 300 mesh iron powder to the citric acid solution according to the molar ratio of iron powder to citric acid of 1:1, keep warm at 80°C with continuous stirring, react for 5 hours to obtain a suspension, then add 10.5 ml of 30% hydrogen peroxide by mass fraction, react for 0.5 hour to obtain solution B;

[0081] S3, solution A and solution B are mixed evenly, and then 0.025 mol of sodium pyrophosphate is added, wherein the molar ratio of sodium to iron in the solution is 4:3, and after sufficient stirring, a uniform dark green solution C is obtained;

[0082] S4. Solution C is spray-dried to obtain a precursor powder with an outlet temperature of 120°C. The precursor powder is then placed in argon protection and pre-fired at 380°C for 3 hours with a heating rate of 5°C / min. The pre-fired powder is ground and then sintered in argon with a heating rate of 5°C / min. It is kept at 565°C for 10 hours to obtain a finished Na4Fe3(PO4)2P2O7 / C composite material.

[0083] Comparative Example 1

[0084] Compared with Example 1, the phosphoric acid concentration of the phosphoric acid solution in step S1 was adjusted to 80wt%, and other operations were the same as Example 1. The process of dissolving iron powder in the phosphoric acid solution was accompanied by the generation of some white floccules, which gradually turned into a thick white suspension, and the experiment failed.

[0085] Comparative Example 2

[0086] Compared with Example 1, the molar ratio of iron element to phosphorus element in step S1 is adjusted to 1:2 in this comparative example. The other operations are the same as those in Example 1. In the early stage of the pre-reaction, as the iron powder is partially dissolved, a green solution is obtained. However, as the iron powder continues to dissolve, a white precipitate begins to form, and finally becomes a thick white suspension. The experiment fails.

[0087] Comparative Example 3

[0088] Compared with Example 1, in this comparative example, all the raw materials of step S1 and step S2 are mixed, specifically, iron powder is added after the phosphoric acid solution and citric acid are mixed. As the reaction proceeds, part of the iron powder dissolves, and the solution begins to produce a black precipitate. As the iron powder further dissolves, more and more black precipitate is produced, and the precipitate cannot be dissolved by adding hydrogen peroxide, and the experiment fails.

[0089] Comparative Example 4

[0090] Compared with Example 1, the slow dropwise addition of the sodium carbonate solution in step S3 was adjusted to a rapid or all-at-one addition of the sodium carbonate solution, and a green suspension was obtained after sufficient stirring, and the experiment failed.

[0091] Comparative Example 5

[0092] According to the molar ratio of sodium, iron and phosphorus being 4:3:4, sodium carbonate, iron phosphate and ammonium dihydrogen phosphate were weighed and added to 5L of water in sequence, stirred and mixed evenly, and the solid content was 25%, and hydrothermally reacted at 180°C for 15h to obtain a primary particle precursor;

[0093] The primary particle precursor was mixed with 10% glucose by weight to obtain a solid content of 45%, and spray-dried to obtain a spherical precursor. The compressed air was preheated at 150°C before entering the spray gun, the nozzle diameter was 2.0 mm, the inlet temperature of the spray drying was 180°C, the outlet temperature was 110°C, and the spray feed flow rate was 1500 mL / h;

[0094] The spherical precursor was heated to 350°C at a rate of 3°C / min in a high-purity nitrogen atmosphere and kept warm for 3.5 hours, and then heated to 700°C and kept warm for 10 hours to obtain a spherical sodium iron phosphate pyrophosphate positive electrode material.

[0095] Comparative Example 5 produces alkaline sodium ferric pyrophosphate, while the present invention produces neutral sodium ferric pyrophosphate.

[0096] The material balance formula of the present invention is: 1.33Fe(H2PO4)2+1.33H3PO4+2Na2CO3+1.67FeC6H5O7+1.67e - →Na4Fe3(PO4)2P2O7+2CO2+1.67C6H7O7 - (dihydrogen citrate) + 3H2O;

[0097] The material balance formula of Comparative Example 5 is: 3FePO4+2Na2CO3+NH4H2PO4+3e - →

[0098] Na4Fe3(PO4)2P2O7+NH3+CO2+CO3 2- +OH - +H2O.

[0099] According to the above material balance formula, the residual dihydrogen citrate of the present invention is acidic (pH 3-4), no alkaline anions remain, and the pH of the calcined product is 7. The residual carbonate and hydroxide ions in Comparative Example 5 are relatively alkaline, and the calcined product is also strongly alkaline (pH = 10-11). Strong alkaline materials easily lead to gelation of the positive electrode slurry and batch failure, which is an unavoidable problem in the existing process for preparing sodium ferric pyrophosphate.

[0100] The carbon content, compacted density and electrochemical performance of the composite materials prepared in all the above examples were tested. The test results are shown in Table 1.

[0101] The composite material obtained in the above embodiment was made into a positive electrode sheet, wherein all the positive electrode sheets were prepared by mixing the active material, Super P, and binder (PVDF) in a mass ratio of 8:1:1, that is, 1.6 g of positive electrode material and 0.2 g of Super P were weighed and put into a mortar and manually ground and mixed evenly, and then transferred to a stirred reactor, and then 3.34 g of PVDF (PVDF mass fraction 6%, solvent is NMP) and 2.8 g of N-methylpyrrolidone (NMP; Place the stirred reactor in a planetary vacuum mixer and stir and grind for 1 hour according to the following procedure: stir at 150 rpm for 10 minutes, stir at 400 rpm for 40 minutes, and stir at 150 rpm for 10 minutes, so as to obtain a mixture slurry with uniform mixing and moderate viscosity. Use a coating machine to evenly apply the slurry on the matte surface of the aluminum foil, dry it at 120°C for 30 minutes, and then move it to an oven to dry it at 80°C for 12 hours. The dried electrode sheet is rolled and compacted by a roller press. After that, it is punched and cut into discs with a diameter of 12 mm by a punching machine. The cut electrode sheet is weighed on a high-precision electronic balance, packaged and marked, and placed in a vacuum drying oven at 80°C to remove surface moisture for use in battery assembly.

[0102] The assembled batteries are all CR2032 button cells. All batteries are assembled in a glove box filled with Ar atmosphere and with a water and oxygen content of less than 0.1ppm. The sodium ion half-cell is assembled by stacking the negative electrode shell, shrapnel, gasket, and sodium sheet in sequence, dripping about 40μL of electrolyte (1mol / L NaClO4 dissolved in EC / PC (1:1vt%) solvent and adding 5vt% FEC as an additive), and then placing a glass fiber separator (Whatman, GF / D), 60μL electrolyte, positive electrode sheet, and positive electrode shell in sequence, and finally pressurizing and sealing with a button battery sealing machine, removing the sealed battery, and wiping the excess electrolyte on the surface to obtain a sodium ion button half-cell.

[0103] At room temperature, the packaged button cell was left to stand for 10 hours, and then charged and discharged at a constant current of 0.1C (1C=129mA / g) in the voltage range of 1.5-4.3V.

[0104] Table 1 Performance data of positive electrode materials for sodium ion batteries in Example

[0105]

[0106]

[0107] XRD analysis was performed on the sodium iron phosphate pyrophosphate products prepared in all the above examples 1-7. The results are as follows: Figure 1 It can be seen that the materials synthesized by the process of the present invention have no impurity peaks and are pure phase sodium iron phosphate pyrophosphate.

[0108] The sodium iron phosphate pyrophosphate products prepared in Examples 1 and 7 were analyzed by scanning electron microscopy. Figure 2 shown. Figure 2 This is a SEM image of the material prepared in Example 1. It can be seen that the material has a regular spherical morphology. Figure 3 This is the SEM picture of the material prepared in Example 7, and its morphology is irregular block-shaped. The key to the different morphologies of the two materials is whether there is a pre-burning process. The material that has been pre-burned and then finally fired has an appearance of black powder without hard lumps, a regular spherical morphology, and better electrochemical performance, with a discharge specific capacity of 108.5mAh g-1 at a rate of 0.1C. The material of Example 7 is obtained by one-step sintering, has an appearance of black hard lumps, and has an irregular block-shaped morphology, and needs to be crushed, ground and sieved before being made into electrode sheets. This shows that the pre-burning process is a more preferred solution.

[0109] In Example 8, manganese is additionally added, and the performance of the carbon-containing composite material finally obtained is better, which is a more preferred solution.

[0110] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: include: S1, reacting iron with a phosphoric acid solution to form a mixed solution of phosphoric acid and ferrous dihydrogen phosphate as solution A; S2, reacting iron with citric acid solution to form a suspension, then adding hydrogen peroxide to mix or introducing air to obtain solution B; S3, mixing solution A, solution B and a sodium source uniformly to obtain solution C; S4, drying solution C to obtain a precursor powder, and sintering to obtain a carbon-containing composite material; Wherein, in steps S1-S3, the molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron and phosphoric acid is 4:3:

4.

2. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step S1, the molar ratio of phosphoric acid to iron is (2.5-5):1, preferably, the molar ratio of phosphoric acid to iron is (2.5-3.5):

1.

3. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step S2, the molar ratio of citric acid to iron is (1-5):1, the molar ratio of hydrogen peroxide to iron in hydrogen peroxide is (1.5-8):1, and preferably, the molar ratio of hydrogen peroxide to iron in hydrogen peroxide is (1.5-5):

1.

4. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step S3, the sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium acetate, sodium dihydrogen phosphate, disodium monohydrogen phosphate, sodium hydroxide, sodium citrate and sodium pyrophosphate.

5. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step S4, the sintering temperature is 400-600° C., preferably, the sintering temperature is 500-600° C.; The heating rate during sintering is ≤10°C / min, preferably, the heating rate during sintering is ≤5°C / min; The sintering time is 6 to 16 hours, preferably 8 to 12 hours. The sintering atmosphere is an inert gas atmosphere.

6. The method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 5, characterized in that: Step S4 also includes a pre-burning operation, including: After the solution C is dried, the precursor powder obtained by drying is pre-fired in a protective gas, and the pre-fired powder is then sintered.

7. The method for preparing a positive electrode material for a sodium ion battery according to claim 6, characterized in that: In step S3, solution A, solution B, a sodium source and a soluble manganese source are uniformly mixed to obtain solution C, wherein the molar ratio of the sum of iron element and manganese element to sodium element and phosphorus element is 3:4:

4.

8. A sodium ion battery positive electrode material, characterized in that: The Na4Fe3(PO4)2P2O7 / C composite material is prepared by the preparation method of the sodium ion battery positive electrode material according to any one of claims 1 to 6.

9. A sodium ion battery positive electrode material, characterized in that: The Na4Fe x Mn 3-x (PO4)2P2O7 / C composite material, 0<x<3.

10. An application of a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material according to claim 8 or 9 is used to prepare a sodium ion battery.